RB1 and Beyond: Determining genetic causes of retinoblastoma in South African patients - Beukman, Danielle (University of the Witwatersrand, Johannesburg, 2024)
Retinoblastoma is the most common solid tumour of the retina, affecting mainly paediatric patients. Although loss-of-function germline variants the RB1 gene is the tumour suppressor gene most often associated with heritable retinoblastoma, two contradictory research findings complicate the assumption that a pathogenic germline variant in RB1 will lead to the development of heritable retinoblastoma. Firstly, heritable retinoblastoma has been observed in cohorts with biallelic wild-type RB1 genes, secondly, biallelic loss-of-function is not always sufficient to lead to retinoblastoma tumorigenesis. By investigating germline variants in additional cancer predisposition genes to discover candidate driver genes in heritable retinoblastoma, the full germline mutational spectrum of heritable retinoblastoma can be established. In this study we investigate sequence germline variants in cancer predisposition genes beyond RB1 in South African retinoblastoma patients with an African ancestry by performing whole exome sequencing on eight patients diagnosed with retinoblastoma. Whole exome sequencing data for genes previously associated with retinoblastoma was subjected to variant annotation by means of a variant effect predictor and filtering criteria applied manually. Variant classification was performed according to guidelines proposed by The American College of Medical Genetics and Genomics and the Association of Molecular Pathology. The highest degree of variant classification was variants of unknown significance. The absence of sequence variants capable of describing the retinoblastoma phenotype in this cohort demonstrates the necessity of looking beyond RB1, combining next generation sequencing with copy number analysis pipelines and additional genome mapping technologies capable of detecting structural variants. The detection of sequence variants previously reported to be possibly damaging but now considered polymorphisms highlights the importance of revisiting variant classification. In closing, this study adds genomic information from patients with a South African ancestry to mounting genomic data, ensuring that previously underrepresented populations can also benefit from future cancer predisposition and precision medicine research.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Medicine Genomic Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Retinoblastoma; RB1 gene; Whole exome sequencing; Cancer predisposition genes; Germline variation; UCTD; SDG-3: Good health and well-being